S-COMMERCE AND DIGITAL MARKETING TRANSFORMATION THROUGH TIKTOK PLATFORM - Yuliani, Fitria; Sri Dwi Fajarini; Juliana Kurniawati (Journal of Economic and Economic Policy, 2025)
Objective: Nowadays, people view TikTok not just as an entertainment medium, but as a key platform driving the growth of S-Commerce. Through TikTok, people can easily market, promote, and buy goods. TikTok has also become a very promising platform for business and marketing by business actors. Method: This study uses a qualitative approach with literature review analysis, utilizing secondary data from articles, books, journals, and research reports. Researchers analyze TikTok’s role in S-Commerce by observing interactions related to marketing, purchases, promotions, and user-generated references, structuring findings into a systematic framework. Results: S-Commerce through the TikTok platform shows a form of digital marketing transformation where there is a change in the form of marketing which is not only centered on sellers in marketing and promoting products through buying and selling platforms but collaborates with users. Novelty: TikTok enables social media and e-commerce activities to be combined in one platform with the efficiency and convenience it offers.